The influence of the land–sea breeze on coastal upwelling systems: locally forced vs internal wave vertical mixing and implications for thermal fronts. (August 2022) - Fearon, Giles; Herbette, Steven; Veitch, Jennifer; Cambon, Gildas; Vichi, Marcello
Abstract: Land–sea breeze forcing near a land boundary drives both a locally forced response and an associated offshore propagating internal wave response, the effects of which can be difficult to separate. These processes enhance vertical mixing near the critical latitude for diurnal-inertial resonance (30° N/S), and are a feature of all four major eastern boundary upwelling systems. Here, we employ 1D- and 2D-vertical model configurations forced by a land–sea breeze to quantify the relative contributions of the locally forced and internal wave responses to surface currents and vertical mixing, and test sensitivity to latitude and bottom slope. We further include a sub-inertial alongshore wind to consider the role of the land–sea breeze in the context of upwelling systems. At the critical latitude, the internal waves generated via thermocline pumping near the land boundary are evanescent (in agreement with theory) and largely absent ∼ 50 km offshore. The internal waves are shown to contribute to vertical mixing, which can be ∼ 20% greater than that due to the forced response alone, further deepening the surface Ekman boundary layer. This deepening reduces the sub-inertial offshore advection of surface waters, thereby retaining the upwelling front closer to the land boundary and driving a net warming of the nearshore surface waters. Cross-shore horizontal oscillations of the upwelling front generated by the land–sea breeze drive strong diurnal variability in sea surface temperature, in agreement with observations from a cross-shore mooring array in the southern Benguela ( ∼ 32.3° S). Highlights: Latitudinally dependent diurnal wind-driven internal waves enhance vertical mixing. Vertical mixing drives surface layer retention and coastal warming during upwelling. Diurnal wind-driven oscillations of the upwelling front explain observed temperatures. Bottom slope steepness controls internal wave generation at the coast.